2020
DOI: 10.1007/s00784-020-03531-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and poor glycemic control increase the occurrence of coronal and root caries: a systematic review and meta-analysis

Abstract: Objectives To assess the occurrence of coronal and root caries in adults with diabetes mellitus (DM).Materials and methods This study was performed accordingly to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. A search strategy was adapted for six databases, as well as gray literature. The risk of bias was assessed using the Joanna Briggs Institute critical appraisal tools for observational studies. Revman 5.3 was used to conduct five metaanalyses. The quality of evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
0
24
1
Order By: Relevance
“…The survival rate analysis regarding IL in uncontrolled DM2 compared to nondiabetic controls was also not statistically significant. The present results disagree with the majority of studies regarding the unsatisfactory outcomes of dental treatments in uncontrolled DM2 [ 31 – 33 ]. However, it is essential to consider that the 3 studies in the meta-analysis were heterogeneous in the methods, and this meta-analysis reported a high level of heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The survival rate analysis regarding IL in uncontrolled DM2 compared to nondiabetic controls was also not statistically significant. The present results disagree with the majority of studies regarding the unsatisfactory outcomes of dental treatments in uncontrolled DM2 [ 31 – 33 ]. However, it is essential to consider that the 3 studies in the meta-analysis were heterogeneous in the methods, and this meta-analysis reported a high level of heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
“…Hyperglycemia is a risk factor for advanced dental treatments that require a satisfactory inflammatory system [ 36 – 39 ]. The main oral issues associated with DM2 are the high incidence of carious lesions, higher prevalence of endodontic problems, and periodontal disease [ 7 , 31 , 40 ]. Thus, edentulism becomes one of the main consequences for these patients [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes mellitus was not associated with tooth extraction due to dental caries in the current study. Although some studies [7,8] have reported an association between diabetes mellitus and dental caries, others [6] have reported no association. The relationship between diabetes mellitus and dental caries is not as strong as that of diabetes mellitus and periodontal disease.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have also reported an association between dental caries and diabetes mellitus [6][7][8]. De Lima et al [7] reported that dental caries was more prevalent among patients with diabetes mellitus than among healthy controls. Lattie et al [8] found that the Decayed, Missing, and Filled Teeth index in patients with diabetes mellitus was twice as high as that in patients without diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation